ABUSE OF POWER DALAM KONTESTASI PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2024 - Achmad Syahril Romdhani; Muhammad Hasan Muaziz (AL WASATH Jurnal Ilmu Hukum, 2025)
Juridical review related to the analysis of Agrarian conflict in Depok City needs to be analyzed more deeply to later be able to find out the causes of Agrarian Conflict in Depok City. This research method uses a normative legal research approach that analyzes the law first, followed by exploring secondary data obtained from journals. and books which are of course related to the Agrarian Conflict and use tertiary data sourced from reliable news reports. The results of this research show that Agrarian Conflict is an obstacle in realizing Agrarian Reform which aims to reduce inequality in control and ownership of land in Depok City, therefore to realize Agrarian Reform what must be resolved first is Agrarian Conflict so that inequality in control of land is truly eliminated. and the realization of better structuring of the structure of control, ownership, use and utilization of land that is more equitable for the prosperity of the people.